Efektivitas Pemberian Kompres Hangat Dan Olesan Minyak Zaitun Terhadap Pengurangan Nyeri Punggung Pada Ibu Hamil Trimester Iii Di Bpm Esther Febriyanti Harahap Kabupaten Asahan Tahun 2024 - Pohan, Atika; Mahyunidar; Wilda Nurfadila Tanjung (Universitas Sari Mutiara Indonesia, 2024)
Back pain is a problem that often occurs in pregnancy, especially in the third trimester of pregnancy. The phenomenon of back pain is one of the most frequently reported complaints among pregnant women. Back pain is caused by the weight of the enlarging uterus and back pain will increase when doing activities. To determine the effectiveness of giving warm compresses and applying olive oil to reduce back pain in third trimester pregnant women. The research design used was pre-experimental and the design used was one group pre-test-posttest design, carried out by one group without a control or comparison group. The sample for this study was 30 pregnant women who complained of back pain. The instrument used for observation sheets and statistical tests is the Wilcoxon test because the data is not normally distributed. Back pain before the intervention with warm compresses and rubbing olive oil was 4.73 (moderate pain) and after the intervention was 1.43 (mild pain). There is an effect of warm compresses and applying olive oil on reducing back pain in third trimester pregnant women at BPM Esther Febriyanti Harahap, Rawang Panca Arga District, Asahan Regency in 2024 with a p value of 0.000. It is hoped that the results of this research will be used to increase insight and knowledge and be used as consideration for choosing non-pharmacological treatments for back pain that can be done at home.